Functional manifestations of early knee osteoarthritis: a systematic review and meta-analysis - Shimizu, Hiroki; Shimoura, Kanako; Iijima, Hirotaka; Suzuki, Yusuke; Aoyama, Tomoki (Clinical rheumatology, 2022)
Early detection of knee osteoarthritis (KOA) can improve treatment outcomes and prevent its progression. The aim of this systematic review was to identify the functional changes in early KOA. Electronic journal databases and platforms, including PubMed, the Physiotherapy Evidence Database, the Cochrane Central Register of Controlled Trials, and Scopus were searched. The inclusion criteria were as follows: (1) studies comparing patients with early KOA with an age-matched control group and (2) studies with objectively measured functional changes as outcomes. Studies that included individuals with Kellgren and Lawrence (K/L) grades > 2- were excluded. A random-effects model was constructed to calculate pooled standardized mean differences (SMDs). A total of nine articles were included in this systematic review. Seven studies used classification criteria to define early KOA, including knee pain; a K/L grade of 0, 1, or 2- (osteophytes only) for the medial compartment; and the presence of two out of four MRI criteria. The remaining two studies included K/L grade 1 confirmed by radiography. Early KOA participants had a significantly longer timed up-and-go test (TUG) time (pooled SMD: 0.57; 95% confidence interval: 0.15, 0.98). The two groups had similar knee extension muscle strength at 90° knee flexion. The quality of evidence for each measured outcome was “very low.” In this review, longer TUG was identified as a functional manifestation of early KOA. Further studies involving functional assessments are needed to develop a screening method to detect early KOA. Key Points • There is a need for diagnostic criteria that include functional changes in patients with early knee osteoarthritis, since radiographic facilities are not available everywhere. • In this review, a long timed up-and-go test time was identified as a functional manifestation of early knee osteoarthritis. • If the findings of this study can be replicated, measurement of TUG may allow for earlier detection of knee osteoarthritis outside the hospital and in routine clinical practice without the use of MRI or X-rays.